Sad Dharma As A Learning Method Of Hindu Religious Education And Character Of 2013 Curriculum In SMP Gurukula Bangli - Ni Komang Sutriyanti; Marsono Marsono; I Nyoman Alit Supandi (Institut Hindu Dharma Negeri Denpasar, 2019)
The success of an education is largely determined by many factors, some of the factors in supportingthese successes are the quality of human resources (HR), facilities, infrastructure, and the curriculum used. The change in curriculum requires teachers to understand and be able to implement all these changes in the learning process in the classroom, but not many teachers understand and are able to implement these changes in learning activities, especially in the use of learning methods. Therefore, this paper will attempt to examine the Sad Dharma method of learning of Hindu religious education and character entitled